Migração familiar e trabalho infantil no Brasil Urbano - Mesquita, Shirley Pereira de (2011)
The main objective of this study is to examine how parents allocate time for children aged from 10 to 14 years-old between study and work in urban Brazil, considering, among other possible determinants, the condition of intersectoral migration of the family. Thus, we used data from the IBGE Census 2000. The empirical analysis was divided into two parts. First, we used a model of joint determination of employment and income of parents, decomposing then, the wage gap condition of migration. Secondly, a probit bivariate model was employed for joint determination of the probability of school attendance and child labor, which, together with an extension of the Oaxaca-Blinder decomposition, allowed to calculate the differential probability attributed to the condition of migrating parents. The results showed that formal education is the main determinant of the probability of work and level of parental income. It is noteworthy, first, the selectivity of negative fathers and mothers in rural-urban migrants attributes not observed, and secondly, the positive, the urban-urban migrant parents, when compared to urban natives. At the time allocation of children, the main determinant is the level of parental education, showing a negative correlation with the probability of working and positive with the probability of school attendance. The attractiveness of local markets has also proved important in determining child labor. The calculation of decomposition of the differential probabilities showed that the condition of migration impact on parental time allocation of children, ie, migrant children are studying less and working more than the children of natives, with the observation that the effect of migrant status is more influential on the children of rural-urban migrants, especially if they are in one-parent family unit under the responsibility of the mother. Finally, the findings revealed that the residence time of the family in town has a positive effect on children, particularly with respect to the probability of studying.